Embodying Black religions in Africa and its diasporas - Covington-Ward, Yolanda; Jouili, Jeanette S. (Religious cultures of African and African diaspora people, 2021)
Foreword / Jacob Olupona, Harvard University, Divinity School -- Introduction: Embodiment and relationality in religions of Africa and its diaspora / Yolanda Covington-Ward and Jeanette S. Jouili -- Spirited choreographies : embodied memories and domestic enslavement in Togolese mama tchamba rituals / Elyan Hill -- Alchemy of the fuqara : spiritual care, memory, and the Black Muslim body / Youssef Carter -- Spiritual ethnicity : our collective ancestors in Ifá devotion across the Americas / N. Fadeke Castor -- Faith full : sensuous habitus, everyday affect, and divergent diaspora in the UCKG / Rachel Cantave -- Covered bodies, moral education, and the embodiment of Islamic reform in northern Nigeria / Elisha P. Renne -- Embodied worship in a Haitian protestant church in the Bahamas : religious habitus among Bahamians of Haitian descent / Bertin M. Louis Jr. -- The quest for spiritual purpose in a secular dance community : Bèlè's rebirth in contemporary Martinique / Camee Maddox-Wingfield -- Embodying Black religion : the ethics and aesthetics of Afro-diasporic Muslim hip-hop in Britain / Jeanette S. Jouili -- Secular affective politics in a national dance about AIDS in Mozambique / Aaron Montoya -- Wrestling with homosexuality : kinesthesia as resistance in Ghanaian pentecostalism / Nathanael Homewood -- "Exceptional healing" : gender, materiality, embodiment, and prophetism in the Lower Congo / Yolanda Covington-Ward -- Dark matter : formations of death pollution in southeastern African funerals / Casey Golomski.